2021
DOI: 10.1111/1753-0407.13147
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of once‐weekly dulaglutide in adult Chinese patients with type 2 diabetes and lower baseline body mass index

Abstract: Highlights In Chinese patients with type 2 diabetes (T2D) and body mass index (BMI) <25 kg/m2, dulaglutide demonstrated great improvements in glycemic control with mild body weight reduction and low hypoglycemia risk. The results indicate that dulaglutide is effective and safe in patients with T2D and lower BMI; therefore, BMI should not be a consideration when dulaglutide is prescribed to Chinese patients with T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Dulaglutide achieved a greater HbA1c reduction, combined with weight loss and lower risk of hypoglycemia, compared with active comparators (glimepiride and insulin glargine) regardless of baseline HbA1c; patients with a higher baseline HbA1c did achieve greater HbA1c reductions [ 26 ]. In the same Chinese populations, another post-hoc analysis showed that dulaglutide improved glycemic control combined with a slight body weight reduction and low hypoglycemia risk in patients with a BMI < 25 kg/m 2 ; this result suggests that BMI is not a necessary consideration for dulaglutide treatment in Chinese patients with T2DM [ 27 ]. In the present study, baseline HbA1c levels were patient-reported, with a mean value of 8.8% and a mean BMI of 28.1 kg/m 2 ; these values indicate that Chinese diabetologists tend to prescribe dulaglutide for relatively obese patients or for patients with higher HbA1c in real-world clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Dulaglutide achieved a greater HbA1c reduction, combined with weight loss and lower risk of hypoglycemia, compared with active comparators (glimepiride and insulin glargine) regardless of baseline HbA1c; patients with a higher baseline HbA1c did achieve greater HbA1c reductions [ 26 ]. In the same Chinese populations, another post-hoc analysis showed that dulaglutide improved glycemic control combined with a slight body weight reduction and low hypoglycemia risk in patients with a BMI < 25 kg/m 2 ; this result suggests that BMI is not a necessary consideration for dulaglutide treatment in Chinese patients with T2DM [ 27 ]. In the present study, baseline HbA1c levels were patient-reported, with a mean value of 8.8% and a mean BMI of 28.1 kg/m 2 ; these values indicate that Chinese diabetologists tend to prescribe dulaglutide for relatively obese patients or for patients with higher HbA1c in real-world clinical practice.…”
Section: Discussionmentioning
confidence: 99%